Design of A Website-Based Internship Information System (Case Study of Industrial Engineering UPN “Veteran” East Java) - Kartikasari, Bintang Andita; Donoriyanto, Dwi Sukma (The Indonesian Journal of Computer Science, 2023)
The Industrial Engineering Study Program is one of the study programs at the Faculty of Engineering, UPN "Veteran" East Java. In the teaching and learning process, students are required to undertake an internship as a graduation requirement. Currently, the training administration still relies on manual processes, which results in the administration process needing to be more effective and efficient. Given these problems, an internship information system will be produced. This website-based internship information system is implemented so that anyone can access the website anytime and anywhere. Therefore, the relevant parties can access this internship information system more efficiently. The research method for collecting the required data is observation and interviews. This information system uses PHP programming language and MySQL as the database. Based on the results of the tests that have been carried out, this website-based internship information system makes it easier for related parties to administer internship activities. Students can apply for supervisors' internship seminars and upload internship grades, and admins can plot supervisors, provide assignment letters for supervisors, and plot examiners online and systematically